Dynamically regulated sumoylation of HDAC2 controls p53 deacetylation and restricts apoptosis following genotoxic stress - Brandl, André; Melchior, Frauke (Journal of molecular cell biology, 2012)
Abstract: Histone deacetylase 2 (HDAC2) is relevant for homeostasis and plays a critical role in gastrointestinal cancers. Here, we report that post-translatio
Published online April 5, 2012
Gesehen am 18.06.2018